Estudo clínico comparativo entre sutura convencional e vaporização a laser de dióxido de carbono (CO2) em pele de ratos - Paes Júnior, Tarcisio José de Arruda [UNESP] (2000)
The proposal of this study was to compare a wound healing between conventional suture and vaporization with CO2 laser in rats skin. ln such case 24 rats were utilized, making two longitudinal incisions in dorsum by scalpel. ln the left side incision the wound was sutured with nylon thread. ln the right side incision the wound were close by approach and vaporized with C02 laser, defocusing, 8 watts in continuous mode. The wound healing was followed by clinical photographic taking at the times: immediately after the procedure, 24 hours, 3, 7, 14, and 21 days. The results showed an early delay of reparation in healing vaporized in comparison with the sutured one, however occurred 21 days both repair tissue showed the same clinical characteristic. This results suggested that the C02 laser can be used by eventual substitute of suture.